2016
DOI: 10.1590/s1806-92902016000900010
|View full text |Cite
|
Sign up to set email alerts
|

Performance and metabolite profile of dairy cows fed tropical grasses and concentrates containing crude protein with low or high degradability

Abstract: -Ten Holstein-Zebu crossbred cows distributed into two simultaneous Latin squares (5 × 5) as a 2 × 2 factorial arrangement formed by chopped sugarcane or elephant grass silage, both with high or low protein degradability supplements and a corn silage as a control treatment, were compared using orthogonal contrasts. The studied variables were the performance, plasma concentrations of urea-N, glucose, and creatinine, urine-N and milk urea-N, and the nychthemeral variation in NH 3 -N in the rumen fluid of dairy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Perhaps the higher diet CP concentration with the sugarcane diet contributed to the increased MUN concentration. A similar finding was reported by Gomes et al (2016), who observed a higher concentration of MUN in dairy cows with diets based on sugarcane compared with diets based on maize silage at the same level of milk production. Gomes et al (2016) also found better use of N with diets based on maize silage, with a R : C ratio of 780 : 220 g/kg, due to lower N-urea losses in plasma, urine and milk compared with a sugarcane-based diet (R : C ratio of 600 : 400 g/kg) or with a diet based on elephant-grass silage (R : C ratio of 760 : 240 g/kg).…”
Section: Milk Compositionsupporting
confidence: 88%
See 3 more Smart Citations
“…Perhaps the higher diet CP concentration with the sugarcane diet contributed to the increased MUN concentration. A similar finding was reported by Gomes et al (2016), who observed a higher concentration of MUN in dairy cows with diets based on sugarcane compared with diets based on maize silage at the same level of milk production. Gomes et al (2016) also found better use of N with diets based on maize silage, with a R : C ratio of 780 : 220 g/kg, due to lower N-urea losses in plasma, urine and milk compared with a sugarcane-based diet (R : C ratio of 600 : 400 g/kg) or with a diet based on elephant-grass silage (R : C ratio of 760 : 240 g/kg).…”
Section: Milk Compositionsupporting
confidence: 88%
“…A similar finding was reported by Gomes et al (2016), who observed a higher concentration of MUN in dairy cows with diets based on sugarcane compared with diets based on maize silage at the same level of milk production. Gomes et al (2016) also found better use of N with diets based on maize silage, with a R : C ratio of 780 : 220 g/kg, due to lower N-urea losses in plasma, urine and milk compared with a sugarcane-based diet (R : C ratio of 600 : 400 g/kg) or with a diet based on elephant-grass silage (R : C ratio of 760 : 240 g/kg). Santiago et al (2013), using urea and ammonium sulphate levels (9 : 1 w/w) in the diet of dairy cows based on sugarcane as roughage, found that up to 12 g/kg of natural sugarcane could be supplied without affecting performance, but with less efficiency in the use of nitrogen ingested.…”
Section: Milk Compositionsupporting
confidence: 88%
See 2 more Smart Citations